The Role of Female Physicians in Psychosomatic Medicine: Opportunities and Challenges - Caroline Rometsch (Mary Ann Liebert, 2024)
Background: Female physicians are in some cases preferred by patients due to their sex-related characteristics such as softness and empathy. Psychosomatic medicine presents a compelling working environment due to its holistic approach. Methods: This brief review synthesizes the challenges encountered by female physicians in psychosomatic medicine and outlines potential strategies for overcoming these barriers. Results: The presence of female role models may constitute a crucial advancement in this process. There exists a pressing demand for specialized clinical and scientific programs in psychosomatic medicine at both national and international levels. Such programs, offered by universities and ministries, as well as comprehensive training initiatives, are indispensable in fostering the next generation of females in psychosomatics. Leading journals can lend their support by publishing special issues dedicated to female physicians. Conclusion: Strengthening female physicians throughout all positions in psychosomatic medicine can contribute ultimately to the improvement of patient care.